Effect of a reducing agent for silver on the electrochemical activity of an Ag/Ba0.5Sr0.5Co0.8Fe0.2O3-d electrode prepared by electroless deposition technique - Zhou, W.; Ran, R.; Cai, R.; Shao, Zongping; Jin, W.; Xu, N. (Elsevier SA, 2009)
Silver-modified Ba0.5Sr0.5Co0.8Fe0.2O3-d (Ag/BSCF) electrodes were prepared using an electroless deposition technique. The morphology, microstructure and oxygen reduction reaction activity of the resulted Ag/BSCF electrodes were comparatively studied using Fourier transform infrared spectra, environmental scanning electron microscopy, temperature-programmed oxygen desorption, X-ray diffraction, and electrochemical impedance spectroscopy. An area-specific resistance as low as 0.038 O cm2 was achieved for N2H4-reduced Ag/BSCF cathode at 600 °C. Carbonates were detected over the BSCF surface during the reduction of silver, which deteriorated both the charge-transfer process and diffusion process of HCHO-reduced Ag/BSCF cathode for the oxygen electrochemical reduction reaction. An anode-supported single cell with an N2H4-reduced Ag/BSCF cathode showed a peak power of 826 mW cm-2 at 600 °C. In comparison, only 672 mW cm-2 was observed with the HCHO-reduced Ag/BSCF cathode. © 2008 Elsevier B.V. All rights reserved.